Dribbling in football: Confronting learning theories - Giordano, L.; Federici, A.; Valentini, M.; D'Elia, F. (Journal of Human Sport & Exercise, 2019)
The football game is the most beloved sport among society, especially for its emotional and recreational worthiness. Dribbling is the most important ability. It is intended to be as the capability of keeping the ball afloat preventing it from touching the ground by using the two lower limbs. The most time the ball lingers afloat, the highest level the doer shows to have achieved. The main point of this research is to spot the most adequate educative method in dribbling. By confronting two different learning methods, I have tried to develop a way of making headways in the above process. On the one hand the cognitive approach in the scientific paradigm turns out to work with a fabricated set of rules within which the little boy must move, whereas in the eco-dynamic approach the heuristic way of learning is followed. The results give out two solutions: the first one shows an increasing ability pursued by gradual repetitions, beginning with a low degree of complexity up until a major difficulty; the last one aims at getting gratification on "no ruling" ground. In the first case, the players must stick to the coach's orders and timing conditions. In the second one the doers are just given the space and tools, neither timing nor conditions are set. They only have to express themselves as much as they like. Both methods grasp to the ordinary educational system.